Measuring the effectiveness of a community engagement theory-driven training program - Gokmenoglu, Tuba; Dasci Sonmez, Elif; Yavuz, İbrahim; Dolunay Cug, Fevziye; Cemaloglu, Necati (International journal of disaster risk reduction, 2025)
Disaster resilience in schools is critical for ensuring safety and preparedness in regions prone to natural disasters. Istanbul, Türkiye's largest economic and cultural hub, is especially vulnerable to such risks, making schools' disaster resilience a pressing concern. This study aimed to evaluate the effectiveness of an in-service training program grounded in Community Engagement Theory, designed to enhance the disaster resilience of teachers and school administrators. The research employed an experimental pretest-posttest control group design, involving 29 teachers and 9 school administrators from 3 schools in the experimental group who participated in a 23-week training program. A 52-item Disaster Resilience Scale for Teachers (DRS-T) was used to assess program outcomes. Data were analyzed using inferential statistical methods. The results indicated that participants in the experimental group exhibited statistically significant positive changes in individual, community, and societal/institutional-level characteristics, with the exception of the responsibility sub-domain. In contrast, the comparison group showed no significant changes, apart from improvements in the intend and positive outcome expectancy sub-domains. These findings highlight the program's effectiveness while underscoring the need to address certain limitations. Recommendations for future research and program enhancements are discussed.